Opposing role of synaptic and extrasynaptic NMDA receptors in regulation of the extracellular signal-regulated kinases (ERK) activity in cultured rat hippocampal neurons - Ivanov, Anton (Blackwell Science Inc, 2006)
The extracellular signal-regulated kinases (ERK) signalling cascade is a key pathway that mediates the NMDA receptor (NMDAR)-dependent neuronal plasticity and survival. However, it is not clear yet how NMDARs regulate ERK activity. Stimulation of the NMDARs induces a complex modification of ERK that includes both ERK activation and inactivation and depends on particular experimental conditions. Here we show that there exists a differential restriction in the regulation of ERK activity that depends on the pool of NMDAR that was activated. The synaptic pool of NMDARs activates ERK whereas the extrasynaptic pool does not; on the contrary, it triggers a signalling pathway that results in the inactivation of ERK. As a result, simultaneous activation of both extrasynaptic and synaptic NMDAR using bath application of NMDA or glutamate (a typical protocol explored in the majority of studies) produced ERK activation that depended on the concentration of agonists and was always significantly weaker than those mediated by synaptic NMDARs. Since the activation of the extrasynaptic NMDA is attributed mainly to global release of glutamate occurring at pathological conditions including hypoxic/ischaemic insults, traumas and epileptic brain damage, the reported differential regulation of ERK cascade by NMDARs provides a unique mechanism for an early identification of the physiological and/or pathophysiological consequences of NMDAR activation. The negative regulation of the ERK activity might be one of the first signalling events determining brain injury and constitutes a putative target of new pharmacological applications.